A study exploring the autism awareness of students attending the department of pre-school teacher education of a public University in Istanbul, Turkey - KARAVUŞ, MELDA; LÜLECİ, NİMET EMEL; HIDIROĞLU, SEYHAN (MARMARA UNIV, FAC MEDICINE, 2020)
Objectives: Early detection of autism might largely depend on pre-school teachers' awareness and their prompt referral of these children to health authorities for accurate diagnosis. The purpose of our study was to assess the awareness about childhood autism among students attending the Department of Pre-school Teacher Education of a public university. Materials and Methods: This descriptive study was carried out on 181 out of 218 students. Results: The best known characteristic of a child having autism was having a hard time in social relations (90.1%). The majority (85.6%) of the study group believed that autism was curable and thought that a child having autism could pursue a family life in the future with his/her spouse (51.3%). Around 60.7% of all participants were of the opinion that a child with autism cannot participate in conversations. Conclusion: The idea of a child with autism disturbing the teaching environment (50.8%) exists which might be a very important obstacle for his/her education; thus interfering with his/her treatment. Autism awareness of respondents could be considered to be relatively good among the senior students.
Keywords: Autism; Awareness; Pre-school Teaching; University Students; GENERAL-POPULATION; SPECTRUM DISORDER; KNOWLEDGE; ATTITUDES; CHECKLIST